YM976 assessment as an alternative to gonadotropic hormones in the in vitro maturation of bovine oocytes and its competence for embryonic development - Carrillo-Gonzalez, Diego Fernando (2021)
The aim of this study was to evaluate the effect of YM976 as a specific inhibitor of phosphodiesterase type 4 (PDE-4) on the in vitro maturation of bovine oocytes and their capacity for embryonic development. For this, cumulus-oocyte complexes were obtained by follicular aspiration of ovaries obtained in a slaughterhouse. They were matured in vitro for 24 hours in TCM-199 medium supplemented with four concentrations of YM976 (1, 10, 100 and 1000 nM) or with gonadotropins (LH and FSH). The expansion of the cumulus was evaluated by visual observation and the resumption of metaphase II by staining with Hoechst dye. The oocytes were fertilized and cultured in KSOM Evolve medium for eight days. The percentage of grade 3 expansion of the cumulus cells in oocytes cultured with gonadotropins was different (p=0.00016) compared to those cultured in the presence of YM976. The resumption of metaphase II was similar between oocytes matured at 10 nM YM976 and those matured with gonadotropins. The oocytes matured in concentrations of 1 and 10 nM of YM976 presented an early embryonic development similar to that found in those matured with gonadotropins. In contrast, high concentrations of YM976 had deleterious effects. In conclusion, concentrations of 1 and 10 nM of the PDE-4 inhibitor YM976 during in vitro maturation of oocytes delay the expansion of granulosa cells, but allow nuclear maturation and competition for embryonic development, similar to oocytes matured with gonadotropins, suggesting that the use of YM976 can be applied in in vitro maturation processes of bovine oocytes.